Pemahaman konsep matematis siswa kelas VII MTs Ma’arif NU Kota Malang materi bilangan berdasarkan teori APOS - Shofia, Rifatul Audia (Maliki Interdisciplinary Journal, 2024)
The background of this study is the low average score of mathematics exams and the prevalence of errors in questions related to the concept of numbers in MTs Ma’arif NU Malang City. This study aims to analyze the understanding of mathematical concepts of grade VII students in the school on number material using the APOS theory approach. The subjects of this study consisted of three students who had different levels of ability, namely high, medium, and low. The selection of subjects is based on the recommendations of the mathematics teacher. Data collection methods used include written tests, interviews, and documentation. The results showed that the three subjects, namelThe background of this study is the low average score of mathematics exams and the prevalence of errors in questions related to the concept of numbers in MTs Ma’arif NU Malang City. This study aims to analyze the understanding of mathematical concepts of grade VII students in the school on number material using the APOS theory approach. The subjects of this study consisted of three students who had different levels of ability, namely high, medium, and low. The selection of subjects is based on the recommendations of the mathematics teacher. Data collection methods used include written tests, interviews, and documentation. The results showed that the three subjects, namely KT, KS, and KR, had not been able to pass the APOS stage in understanding mathematical concepts.y KT, KS, and KR, had not been able to pass the APOS stage in understanding mathematical concepts.